A heuristic study of clients spiritual experiences in the counseling process / Wong Ching Ching - Wong, Ching Ching (2015)

(untitled)
This study addressed and described the spiritual experiences in the psychotherapeutic process. The heuristic inquiry approach was applied to explore the relationship between the clients’ and the therapist’s spiritual experiences with the transpersonal self. The study consisted of seven participants, women aged over 35 who had gone through at least seven psychotherapy sessions with the researcher / therapist. The Satir systemic therapy, existential therapy, the hypnotherapy and expressive arts therapy were among the psychotherapy approaches that generate the spirituality of the participants to connect with the self. The results indicated that all the participants and the therapist were able to engage with their spiritual self in the psychotherapeutic process. The process of transformation and self-integration has taken place during the psychotherapeutic process which enhanced the sense of vocation in the participants’ and the therapist’s life. The spiritual experiences were expressed in explicit and implicit ways. Among the spiritual experiences, there were theistic and non-theistic spirituality as well as humanistic perspective in the concept of individuation and self-actualization. The spiritual experiences were manifested in the form of energy movement and visions that carried messages, the out of space sensation, the chirping sounds of the birds and the sense of stability at the core of the being. The spiritual experiences were also manifested in the form of feelings such as the feeling of warmth, peace, tranquility, love and being touched. Each participant and the therapist have finally illustrated the individual self with the unique self-depiction. The self of each participant was symbolized in the form of a lighted candle, a sailing ship, a little angel, a flying balloon, the integrated colors, a renewed ordinary lady and a blossoming lotus. Whereas the therapist’s self depiction is in the form of a dove. The poem and the drawing depict the psychotherapy journey.